The promise of a park, recreation, and tourism education in a participatory democracy. (8th August 2019) - Dustin, Daniel; McDonald, Cary; Wright, Brett; Harper, Jack; Lamke, Gene; Murphy, James
Abstract: We believe the education of future park, recreation, and tourism professionals is incomplete if it does not prepare them for moral leadership in a participatory democracy. We anchor our thinking in Pieper's Leisure: The Basis of Culture and build our case by revisiting Bloom's The Closing of the American Mind, in which he admonished higher education for not preparing students, regardless of major, for assuming responsibility for their country's moral character based upon conscientious consideration of civilization's major philosophical ideas. We then apply Bloom's criticism to the education of park, recreation, and tourism students. Based on our analysis, we implore educators in our field to live up to their educational promise by embracing service learning and community-engaged learning as critical components of our students' professional preparation to ready them for civic engagement as well as a career in parks, recreation, and tourism.